LEVERAGING NEUROPLASTICITY FOR TAILORED LEARNING IN THE INDONESIAN HIGHER EDUCATION CURRICULUM: A MULTIDIMENSIONAL ANALYSIS OF ADAPTIVEPEDAGOGICAL STRATEGIES TO ENHANCE LEARNING OUTCOMES - Diana Evawati; Mahmudah; Agus Ridwan Misbahuddin; Al-Amin; Ika Rahayu Satyaninrum (Adisam Publisher, 2023)
In this comprehensive study, we conducted an in-depth and multidimensional analysis to explore the utilization of adaptive pedagogical strategies in the Indonesian higher education curriculum. Our primary focus was leveraging the fascinating neuroplasticity concept to enhance learning outcomes in this context. The study encompassed a wide array of aspects related to personalized learning, delving into its potential impact on education in Indonesia. One of the central themes of our research was the intricate relationship between neuroplasticity and the tailored learning experiences offered by personalized education. By understanding how the brain's plasticity allows it to adapt and rewire in response to new learning experiences, we aimed to shed light on how personalized learning methods can be further optimized to accommodate the diverse needs of Indonesian students. Furthermore, our study took a meticulous look at the tangible results of these strategies on learning outcomes. We aimed to provide empirical evidence of the effectiveness of personalized and adaptive teaching methods in enhancing students' educational experiences. The assessment considered the diversity of the student population. It sought to measure how these pedagogical strategies positively influenced learning outcomes, ultimately contributing to a more effective and dynamic educational landscape. The implications of our findings are far-reaching, particularly in the context of curriculum design and teaching practices in Indonesian higher education institutions. By illuminating the potential benefits of personalized learning and neuroplasticity-informed pedagogical strategies, this research contributes to the ongoing efforts to enhance the quality and accessibility of education in Indonesia.